2022
DOI: 10.3390/polym14245357
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PLA/PHB Biopolymer Material with Admixture of Hydroxyapatite and Tricalcium Phosphate for Clinical Use

Abstract: One trend in tissue engineering and regenerative medicine is the development of degradable composite polymers. The aim of this study was the comprehensive analysis of Polylactic acid (PLA) / Polyhydroxybutyrate (PHB) + Hydroxyapatite (HA)/ Tricalcium phosphate (TCP) material from filament production to mechanical testing of samples with different infills and the production of an implant replacement for an intervertebral disc. Filament Maker – Composer 450 (3devo; Netherlands) was used to produce filaments. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…The results showed that all samples were safe, resulting in cell viability higher than 70%, similar to control ( Figure 7 ). This result confirmed previous ones that demonstrated no toxicity of biocomposites based on PHB/BC, and PHB blended with different biopolymers, including PLA and Hydroxyapatite (HA) [ 62 , 63 ]. Furthermore, the PHB/BC-based biocomposites proved to support 3T3-L1 preadipocyte proliferation and induced a positive effect on osteoblast differentiation in vivo.…”
Section: Resultssupporting
confidence: 91%
“…The results showed that all samples were safe, resulting in cell viability higher than 70%, similar to control ( Figure 7 ). This result confirmed previous ones that demonstrated no toxicity of biocomposites based on PHB/BC, and PHB blended with different biopolymers, including PLA and Hydroxyapatite (HA) [ 62 , 63 ]. Furthermore, the PHB/BC-based biocomposites proved to support 3T3-L1 preadipocyte proliferation and induced a positive effect on osteoblast differentiation in vivo.…”
Section: Resultssupporting
confidence: 91%
“…The results of the experiment present knowledge about their suitability for clinical use in the human body. A similar topic was addressed by Kohan et al [ 23 ], who performed cytotoxicity and cell proliferation tests on PLA/PHB + HA/TCP polymers using L929 mouse fibroblasts. The results showed that the materials are not cytotoxic, and the metabolic activity of the cells is greater than 70% in all cases.…”
Section: Discussionmentioning
confidence: 83%
“…They investigated mixtures of PLA and PHB materials at different mass ratios, which helped us in the analysis of SEM images. Similarly, Kohan et al [ 23 ] observed the distribution of the ceramic component in the PLA/PHB composite using SEM analysis. Through SEM, Čulenová et al [ 13 ] observed the surface of the PLA/PHB/TPS material and the visible concentration of the cell distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extruder temperature profiles were adjusted to 170, 180, 180, and 195 • C while maintaining a screw speed of 50-60 rpm. The resulting extrudate was cooled through a dual air-cooling system to produce a filament with a diameter of 1.75 mm [38]. The morphology of the generated DCP-PHB/PMMA filament was analysed using a Scanning Electron Microscope (SEM) (HITACHI S-4700, Tokyo, Japan).…”
Section: Filament Fabrication and Sem Analysismentioning
confidence: 99%